Prevalence of conflicts over the legitimacy of election results in Africa : can the regional economic communities (RECs) provide a panacea? A case study of ECOWAS and SADC - Kotey, Nii Ashie (University of Pretoria, 2012)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2011.